A geopoética de Sophia de Mello Breyner Andresen: paisagem e escrita - Silva, Vanessa Correia de Araujo (2019)
This dissertation deals with the experience of landscape in the poetic modernity of Sophia de Mello Breyner Andresen. Its objectives include: reflecting on the experience of landscape as “landscape thinking” in the writing of this poet, analyzing the aesthetic procedures employed in the refiguration of landscape in the poem; to grasp the dialogue with the modern tradition and its relation to the sensible experience in the modernity; analyze the resignification of lyricism and its relation to emotion, to subjectivity, in the light of alterity. To achieve such goals, the following questioning is been proposed: To what extent is perception intrinsic to the construction of the landscape in Sophia, showing an analogy between being in the world and being in writing? How is the landscape in Sophia's poetry revealing experiences with visualities that imply a lyrical relationship between man and the world? Among the guiding hypotheses, the following stand out: the poet reconstructs her kingdom divided from what she sees and hears, generating in the writing process the landscape effect; the poet translates the phisis into landscape thinking, according to the understanding of the revealing perceptual process of sensible experience. As a theoretical foundation, to profile the concept of landscape, we resorted mainly to Michel Collot's reflections from the philosophy of Merleau-Ponty, and to discuss the critical-poetic question, to the reflections of Octavio Paz and Paul Valéry. The study of poems that make up her poetic production is presented in Obra Poética (2015), which brings together, in addition to her fourteen books of poetry, her five poetic arts. The study of the corpus showed, among other considerations, that Sophia's writing builds a gesture of dwelling in writing, as a space and place of the subject in the world, opening new horizons through a geopoetic that is based on the word, reinforcing the desire of search for a meaning for man as a member of the world